Lung cancer and dust exposure: results of a prospective cohort study following 3260 workers for 50 years. Issue 2 (22nd January 2004) - Moshammer, H; Neuberger, M
Abstract : Aims: To study the lasting health impact of occupational dust exposure on life expectancy and specific causes of death. Methods: Male Viennese workers, selected at age ⩾40 (mean 54) years during preventive check-ups between 1950 and 1960, were followed prospectively until death. Half of them (1630) were exposed at work to (non-fibrous) particulates, while the non-exposed workers were matched for year, age, and smoking status at the start of observation. Results: Average life expectancy of those exposed was 1.6 years less than that of those non-exposed. Only a small part of this decrease in life expectancy (hazards ratios in brackets) was related to acknowledged occupational diseases such as silicosis and silicotuberculosis (67.12). Chronic obstructive lung disease (1.82) and cancer of the lung (1.42) and stomach (1.77) were found more frequently among those exposed. Conclusions: Results support the hypothesis that high exposure to insoluble particulates such as silica in the metal, glass, ceramics, and stone industries promotes bronchial cancer and chronic obstructive pulmonary disease. The finding of an increased incidence of stomach cancer might be related to particles swallowed after clearance from the airways.